Fig Pollinating Wasp Transfers Nematodes into Figs of Ficus racemosa in Sumatra, Indonesia - Jauharlina Jauharlina; Rina Sriwati; . Yusmaini; Natsumi Kanzaki; Stephen Compton (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
The fruits (figs) of fig trees (Ficus spp, known as ‘bak ara’ in Aceh), are the source of food for many species of faunas in the forest, including birds, monkeys, orangutans, etc.  Pollination within the figs totally depends on female fig wasps that belong to family Agaonidae. Fig trees and their pollinating wasps rely on each other to survive.  Female fig wasps are known to transport nematodes into receptive figs when the wasps enter the figs to lay  eggs.  An investigation on the nematodes carried by female pollinating wasps Ceratosolen fusciceps Mayr into figs of Ficus racemosa was conducted in Sumatra, Indonesia. The figs on the trees were regularly sampled to determine the presence of nematodes and infer their ecology. The Baermann funnel method was employed to extract the nematodes from the figs.  Eight species of nematodes were recorded from the figs, two of which are still unidentified.  The species found were (1) Teratodiplogaster fignewmani, (2) Teratodiplogaster sp., (3) Parasitodiplogaster sp., (4) Schistonchus sp1., (5) Schistonchus sp2., (6) Mononchoides sp., (7) and (8) two undescribed Diplogastridae species (‘umbrella-like’ species 1 and species 2).  This is the most diverse fig nematode community recorded. The highest nematode populations were routinely found in D-phase figs, when the new generations of wasps were about to emerge.   Details of the ecology of each nematode species are likely to differ, but as a group they did not seem to significantly affect seed and wasp development in F. racemosa figs